Predisposing risk factors for stress fractures in collegiate cross-country runners - Griffin, K. L.; Knight, K. B.; Bass, M. A.; Valliant, M. W. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to explore factors associated with increased stress fractures in collegiate cross-country runners. Subjects in this study were 42 male and female cross-country runners at a Division I university. Each athlete completed a questionnaire regarding smoking status, vitamin/mineral intake, previous stress fracture history, birth control usage, menstrual status, and demographic information. Nutritional assessment using a 3-day food record and measurements of whole body, lumbar spine, and hip bone mineral densities (BMDs) were also conducted on each athlete. Results indicated that 40% of the female and 35% of the male runners reported a history of stress fracture, and that all of them did not meet the recommended daily energy intake or adequate intakes for calcium or vitamin D required for their amount of training. Two-tailed t-test found statistically higher incidences of lumbar spine BMD in male and female runners whose daily calcium and vitamin D intakes were below minimum requirements as well as for women whose caloric intake was below the required level. When data on the lumbar spine was evaluated, 31% of subjects (31.8% of the male and 30% of the female runners) were identified as having osteopenia and 4.8% with osteoporosis. Results warrant a need for future longitudinal studies.